The Relationship Between Teacher and Student in a Phenomenological Key: Changes Brought by Distance Learning - Ferro, Floriana (Scenari, 2023)
This paper draws on previous research carried out by the author on the educative relationship between teacher and student in schools and universities, in order to enrich it with further studies and considerations on distance learning. The author uses the phenomenological method, assuming the point of view of both members of the relationship (student and teacher). The general characteristics of the relationship (reciprocity, asymmetry, and verticality) and the differences between the two parties involved (age and/or developmental stage, educational role, mastery of the discipline, and institutional role) remain, but are articulated differently: this mainly happens, because in distance learning the perception of the body of the other person is partial or absent, hindering the phenomena of pairing and empathy. It is thus shown that distance learning cannot replace face-to-face teaching, however, it is able to support and supplement it.